JAK inhibitors for the treatment of myeloproliferative neoplasms and other disorders - Vainchenker, William (F1000Res, 2018)
JAK inhibitors have been developed following the discovery of the JAK2V617F in 2005 as the driver mutation of the majority of non- BCR-ABL1 myeloproliferative neoplasms (MPNs). Subsequently, the search for JAK2 inhibitors continued with the discovery that the other driver mutations ( CALR and MPL) also exhibited persistent JAK2 activation. Several type I ATP-competitive JAK inhibitors with different specificities were assessed in clinical trials and exhibited minimal hematologic toxicity. Interestingly, these JAK inhibitors display potent anti-inflammatory activity. Thus, JAK inhibitors targeting preferentially JAK1 and JAK3 have been developed to treat inflammation, autoimmune diseases, and graft-versus-host disease. Ten years after the beginning of clinical trials, only two drugs have been approved by the US Food and Drug Administration: one JAK2/JAK1 inhibitor (ruxolitinib) in intermediate-2 and high-risk myelofibrosis and hydroxyurea-resistant or -intolerant polycythemia vera and one JAK1/JAK3 inhibitor (tofacitinib) in methotrexate-resistant rheumatoid arthritis. The non-approved compounds exhibited many off-target effects leading to neurological and gastrointestinal toxicities, as seen in clinical trials for MPNs. Ruxolitinib is a well-tolerated drug with mostly anti-inflammatory properties. Despite a weak effect on the cause of the disease itself in MPNs, it improves the clinical state of patients and increases survival in myelofibrosis. This limited effect is related to the fact that ruxolitinib, like the other type I JAK2 inhibitors, inhibits equally mutated and wild-type JAK2 (JAK2WT) and also the JAK2 oncogenic activation. Thus, other approaches need to be developed and could be based on either (1) the development of new inhibitors specifically targeting JAK2V617F or (2) the combination of the actual JAK2 inhibitors with other therapies, in particular with molecules targeting pathways downstream of JAK2 activation or the stability of JAK2 molecule. In contrast, the strong anti-inflammatory effects of the JAK inhibitors appear as a very promising therapeutic approach for many inflammatory and auto-immune diseases.